Engineering an ultrafine intermetallic eutectic ternary alloy for high strength and high temperature applications. (December 2018) - Tiwary, Chandra Sekhar; Kashiwar, Ankush; Bhowmick, Sanjit; Hari Kumar, K.C.; Chattopadhyay, Kamanio; Banerjee, Dipankar
Abstract: We introduce a novel material based on microstructural engineering of intermetallics at an ultrafine scale. A unique microstructure was developed in a ternary alloy composition (Ni-12 at.% Al-11 at.% Zr) containing two coupled intermetallic phases (Ni3 Al and Ni5 Zr) consisting of colonies with interconnected lamellae that degenerate into irregular morphologies during growth. This architecture exhibits excellent high temperature microstructural stability, exceptional high strength with adequate tensile ductility at room temperature, and outstanding cyclic oxidation resistance. Graphical abstract: Unlabelled Image